Pandangan Islam dan Buddha tentang Nafsu - Harahap, Aprilinda; Zurkarnain, Zurkarnain; Rohilah, Rohilah (Lembaga Yasin AlSys, 2024)
This research aims to find out the similarities and differences in Islam and Buddhism related to lust, namely: first, in terms of understanding lust, these two religions have the same meaning even though they are different in terms of language but have the same meaning if taken from the Koran and Tripikata, because basically it comes from that same root. Second, they both believe that following one's desires will be very detrimental to oneself, even though it is different in terms of what it is called. Both Islam and Buddhism view lust as very dangerous. Both religions both recognize that lust can be controlled with certain methods. Islam views lust as having two characteristics, namely lust which leads to bad and which brings good. Meanwhile, Buddhism views lust as only evil. Apart from that, lust at the end of life in Islam, lust is purified from bad to clean lust, in contrast to Buddhist teachings where lust is eliminated to achieve happiness.